Analisis Rasio Profitabilitas dan Likuiditas untuk Menilai Kinerja Keuangan pada PT. Bukaka Teknik Utama Tbk Tahun 2018-2022 - Putri, Selvina; Nasution, Yenni Samri Julianti (El-Mal: Jurnal Kajian Ekonomi & Bisnis Islam, 2024)
This study aims to analyze the financial performance of PT. Bukaka Teknik Utama Tbk, with a focus on profitability and liquidity ratios during the period 2018-2022. The method used is descriptive with a quantitative approach. This research aims to assess the company's ability to generate profits, meet short-term obligations, and improve its liquidity. The research findings indicate an improvement in profitability over the years, with an average net profit margin of 10.72%. However, operational efficiency remains a concern with an average gross profit margin of 16.95%. While PT. Bukaka Teknik Utama Tbk achieves an average return on assets (ROA) of 9.51%, the average return on equity (ROE) is 17.82%. Additionally, liquidity ratios, including the current ratio, quick ratio, and cash ratio, need to be evaluated to gain a better understanding of the company's financial condition. This study aims to provide deeper insights into the company's financial performance and recommend appropriate improvement measures. Keywords: Profitability, Liquidity, Financial Performance